A Near-Infrared Trace CO2 Detection System Based on an 1,580 nm Tunable Diode Laser Using a Cascaded Integrator Comb (CIC) Filter-Assisted Wavelength Modulation Technique and a Digital Lock-in Amplifier - Li, Guolin; Dong, Enting; Ji, Wen-hai (Frontiers in Physics, 2019)
A near-infrared trace CO2 detection system was experimentally demonstrated based on an 1,580 nm distributed feedback (DFB) laser using a cascaded integrator comb (CIC) filter-assisted wavelength modulation spectroscopy (WMS) technique and a digital lock-in amplifier (DLIA). An 1,580 nm DFB laser emitting at 1,579.1 nm was selected as the light source. A multi-pass cell (MPGC with a 30 m- long path) was adopted as the absorption cell. A DLIA was developed to extract the second harmonic WMS (WMS-2f) signal. The cascade-integrated comb filter (CICF) and the finite impulse response (FIR) low-pass filter (LPF) were combined in the DLIA to improve the performance of DLIA. Three methods of PD (Peak detection), LIA, CICF-assisted WMS, and DLIA were adopted to detect the CO2 concentration levels and the anti-interference performance of each detection method was analyzed. The experimental results indicated that compared with the peak detection and the lock-in amplifier method of the CICF-assisted WMS and DLIA developed in this manuscript had the highest linearity and precision. When the integration time is 3s, the LOD of the system was predicted to be 0.0812 ppm. Due to the advantages of high sensitivity, a low detection limit and a rapid response, the CO2 detection system reported in this manuscript has a good application prospect in the area of oilfield associated gases detection.